Frankies magic football frankie and the dragon curse book 7 - Lampard, Frank (Little, Brown Books for Young Readers London, 2014)
"When Frankie and his friends go to a kung fu lesson to improve their football skills, a giant Chinese puppet magically transports them to the gates of The Forbidden City. The team soon learn that an ancient warrior called Zha-Hu is planning to destroy the Great Wall of China, with help from his dragon and an army of terracotta animals. Can Frankie and his team break the dragon curse in time to stop him?"--Publisher website